2016
DOI: 10.1083/jcb.201509017
|View full text |Cite
|
Sign up to set email alerts
|

Class III myosins shape the auditory hair bundles by limiting microvilli and stereocilia growth

Abstract: Analysis of mice deficient for myosin IIIa and myosin IIIb shows that class III myosins limit the elongation of stereocilia and of subsequently regressing microvilli, thus contributing to the early hair bundle shaping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 60 publications
2
68
1
Order By: Relevance
“…A recent study demonstrated severe defects in stereocilia shape and size in MYO3A Ϫ / Ϫ MYO3B Ϫ / Ϫ double knock-out mice (27). On embryonic stage 16.5 of the double knock-out mice, the cochlear hair bundles showed abnormal shape and exaggerated elongation.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A recent study demonstrated severe defects in stereocilia shape and size in MYO3A Ϫ / Ϫ MYO3B Ϫ / Ϫ double knock-out mice (27). On embryonic stage 16.5 of the double knock-out mice, the cochlear hair bundles showed abnormal shape and exaggerated elongation.…”
Section: Discussionmentioning
confidence: 97%
“…The findings from recent MYO3 studies (25,27,32,34) and an overall growing interest in the function of myosins in actinbased protrusions (8,39,46) demanded a systematic study of the functional differences of MYO3 motor and tail domains. Our results highlight the enhanced motor activity of human MYO3A compared with MYO3B, which correlates with its enhanced ability to localize to actin protrusion tips as well as induce the formation and elongation of actin protrusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While myosin XVa is necessary to elongate stereocilia, increasing stereocilia width depends on myosin IIIa and its paralog myosin IIIb as mice lacking both proteins have longer, thinner stereocilia [55]. Myosin IIIa and myosin IIIb also localize to stereocilia tips along with their binding partner, espin-1, which is the longest splice isoform produced from the transcriptionally regulated Espn gene.…”
Section: Development Of Stereociliamentioning
confidence: 99%